Removal of Remazol Orange RGB from Aqueous Solution by Peanut Shell - Samil, Ali; Acemioglu, Bilal; Gultekin, Gulsah; Alma, M. Hakki (Asian Journal of Chemistry, 2011)
In this study, peanut shell was utilized as an adsorbent for the removal of remazol orange RGB from aqueous solution by adsorption technique. Adsorption experiments were conducted as a function of contact time, initial dye concentration, temperature and pH. While the amount of the dye removed by peanut shell was increasing with increasing contact time, initial dye concentration, solution temperature, it decreased with increasing solution pH. The maximum dye removal were between 82.14 and 97.42 % under all the experimental conditions studied such as concentration, pH and temperature. Adsorption kinetic was in agreement with the pseudo-second order model. Column adsorption studies were also performed and the percentage of dye adsorbed in column was between 98 and 100 % for all studied concentrations.
Keywords: Removal; Peanut shell; Remazol orange RGB; Dye; Kinetics; Column; FTIR; SEM